6分之x-1+2分之3x-1≤2分之3x
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 16:44:36
6分之x-1+2分之3x-1≤2分之3x6分之x-1+2分之3x-1≤2分之3x6分之x-1+2分之3x-1≤2分之3x(x-1)/6+(3x-1)/2≤3x/2x-1+3(3x-1)≤9xx-1+9
6分之x-1+2分之3x-1≤2分之3x
6分之x-1+2分之3x-1≤2分之3x
6分之x-1+2分之3x-1≤2分之3x
(x-1)/6+(3x-1)/2≤3x/2
x-1+3(3x-1)≤9x
x-1+9x-3≤9x
x≤4
去分母得 x+9x-6≤9x
x≤6
6分之x-1+2分之3x-1≤2分之3x
解,得:
(x-1)/6+(3x-1)/2<=3x/2
x-1+9x-3<=9x
x<=4
x-2-x分之3 分之 1+x分之6 +x^2分之5
6分之x-2=x分之x+3-1
(x+2)分之(x+1)-(x+7)分之1=(x+3)分之(x+2)-(x+6)分之1
6分之x-1+2分之3x-1≤2分之3x
6分之2x-5≤4分之3x+1-3分之2x
x+1分之1-x+2分之1-x+3分之1+x+4分之1
(x-1分之2x-x+1分之3x)除以x^2-1分之x
计算 :x-3分之1+(9-x^2)分之6-(6-2x)分之(x-1)
( x-3分之1)+(9-x^2分之6)-(6-2x分之x-1)
6分之X-9-3分之2+X=(x-1) -2分之X-2
3分之x-1减去6分之x+2等于2分之4-x x是多少
2分之1x(6分之5-3分之2)
6分之1x(9分之6+3分之2)
(x^2-x-6分之x^2-4+x-3分之x+2)除以x-3分之x+1
(x²-4分之2x)-(x+2分之1)(x²-4分之2)+(x-2分之x)=1x分之3+x-1分之6=x(x-1)分之x-3
3分之1-2x≤6分之4-3x3分之x-2分之x-1
3分之x*6分之X-1
3分之2x-6分之1x=4分之1x-7分之4×=10分之3